Class of Analytic Function Related with Uniformly Convex and Janowski's Functions. (16th October 2018) - Rasheed, Akhter; Hussain, Saqib; Zaighum, Muhammad Asad; Darus, Maslina
Abstract : In this paper, we introduce a new subclass of analytic functions in open unit disc. We obtain coefficient estimates, extreme points, and distortion theorem. We also derived the radii of close-to-convexity and starlikeness for this class.